Risk factors for dysmenorrhea - رجب, رجاء (Latakia University Journal -Medical Sciences Series, 2023)
Background : Primary dysmenorrhea is a common problem among adolescent females. There are many risk factors in the occurrence of dysmenorrhea some of which can be modified which can lead to improved dysmenorrhea. Objective: we aimed to Determine the prevalence of Dysmenorrhea, in addition to identify the factors that can be considered as risk factors for the occurrence of dysmenorrhoea. Factors studied: age, Family status, presence of children, body mass index, smoking, menstrual abnormalities, puberty age, physical activity of the woman. METHODS: A cross-sectional study with 302 female participants in the Women’s clinic in Tishreen Hospital Between October 2021-October 2022, they answered questionnaire about menstrual characteristics, dysmenorrhea, age, Family status, weight, height,puberty age, smoking, and physical activity. Statistical analysis was performed using multiple linear regression. Results: The ages of the participants ranged between 14-25 years, 48.7% of them suffered from dysmenorrhoea, 30.8% were smokers, 16.9% were overweight, 4% were obese and 10.6% were underweiht. Factors affecting Dysmenorrhea were Menorrhagea and lack of physical activity (pvalue 0.006 for Menorrhagea, pvalue < 0.001 for physical inactivity). Conclusion: Menorrhagea and lack of physical activity can be considered as risk factors for dysmenorrhea and therefore modification of these factors can improve menstruation.